(untitled) (American Journal of Islam and Society, 1992)
In the context of the five-hundred-year anniversary celebrations of the "discovery of the New World" now going on in the United States and Spain, the Syrian Institute for the History of Science (Aleppo University, Aleppo, Syria), organized the Fifth International Symposium of the History of Arab Science in conjunction with the lnstituto de Cooperaci6n con el Mundo Arabe (Institute of Cooperation with the Arab World, the Foreign Ministry of Spain). The theme of the conference, which dealt with the contribution of al Andalus (i.e., Muslim Spain) to the history of science and teclmology, was the obvious reason for this international cooperation between the agencies of Syria and Spain. The contribution of al Andalus in the realms of science and technology to both Muslim and European countries is undeniably important in its own right and should be investigated by similar symposia, not only in Spain or Muslim countries. It was, however, ironic that the fivehundred- year anniversary celebrations of the "discovery of the New World" coincided with the expulsion of Muslims from Spain after the reconquista, not to mention the fact that the "New World" had already been discovered thousands of years before Columbus by the native Americans ...